2008
DOI: 10.1103/physrevlett.101.097601
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Landau-Level Cyclotron Resonance in Bilayer Graphene

Abstract: Interaction driven integer quantum Hall effects are anticipated in graphene bilayers because of the near-degeneracy of the eight Landau levels which appear near the neutral system Fermi level. We predict that an intra-Landau-level cyclotron resonance signal will appear at some odd-integer filling factors, accompanied by collective modes which are nearly gapless and have approximate k 3/2 dispersion. We speculate on the possibility of unusual localization physics associated with these modes.PACS numbers: 76.40.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
223
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(239 citation statements)
references
References 21 publications
15
223
1
Order By: Relevance
“…In this section we show that within the often-used approximation where the difference between interlayer and intra-layer interactions is neglected [4][5][6]13,14 , the interacting Hamiltonian is invariant under rotations in a suitably defined four-dimensional flavor subspace. Specifically, we perform a unitary transformation by exchanging the sublattices A and B in one of the valleys, upon which the single particle Hamiltonian becomes identical for all spin and valley species, while the layer and sublattice blind interactions are left unchanged.…”
Section: Su(4) Symmetrymentioning
confidence: 97%
See 1 more Smart Citation
“…In this section we show that within the often-used approximation where the difference between interlayer and intra-layer interactions is neglected [4][5][6]13,14 , the interacting Hamiltonian is invariant under rotations in a suitably defined four-dimensional flavor subspace. Specifically, we perform a unitary transformation by exchanging the sublattices A and B in one of the valleys, upon which the single particle Hamiltonian becomes identical for all spin and valley species, while the layer and sublattice blind interactions are left unchanged.…”
Section: Su(4) Symmetrymentioning
confidence: 97%
“…Another experimental signature is a phase transition at filling factor ν = 0 and finite B from a QAH state to the Quantum Hall Ferromagnet (QHF) states that are expected to form at large magnetic fields 13 . Such a phase transition would not be seen if the dominant state at small B was of (2,2) type, since the (2,2) states are smoothly connected to the QHF state.…”
Section: Experimental Signatures Of the Qah Statementioning
confidence: 99%
“…The minimization of the interaction energy results in gapped states which break either spin rotation or pseudospin (valley) rotation symmetry, or both. 17,33,35,49,60,61,74 If either the Zeeman energy ∆ Z or the interlayer energy difference u is present, they affect the order how the Landau levels are filled, but exchange energy considerations are more crucial in most cases. 17,68 The most convenient basis in pseudospin space may differ; we may introducê a nSσp = cos θ 2â n,ξ=1,σp + sin θ 2 e iφâ n,ξ=−1,σp ,…”
Section: Quantum Hall Ferromagnetic Statesmentioning
confidence: 99%
“…11 Further broken symmetry states have been observed [12][13][14][15][16] in the central Landau band at ν = 0, ±1, ±2 and ±3, and by careful tilted-field measurements it has been shown that they arise predominantly from many-body effects, i.e., from quantum Hall ferromagnetism (QHF). 17 Quantum Hall states with broken symmetry have also been found in the n = −2 Landau level 18 , and there is also some evidence for a fractional quantum Hall plateau.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation